Social Construction in Plastic Waste Management for Community empowerment And Regional Structure in Pematang Johar Village, Deli Regency, Serdang, North Sumatera - Arifin Saleh; Mujahiddin Mujahiddin; Sigit Hardiyanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The growth rate of plastic waste in Indonesia occurs every year. The Central Statistics Agency (BPS) revealed that plastic waste in Indonesia has reached 66 million tons per year. In Dusun 15 Pematang Johar Village, there is a Suka Mulia Waste Bank which has been established in 2020 and has 60 customers. The presence of this waste bank has changed waste management activities, especially plastics. The villagers have started to actively save waste and turn plastic waste into eco-bricks. The change in waste management in the community makes this research aim to analyze the process of change that occurs using the social construction approach proposed by Berger and Luckmann. The design of this research is qualitative with a descriptive approach. The data in this study consisted of secondary data and primary data, both of which were analyzed using an interactive model as proposed by Miles and Huberman, which consisted of three main things, namely: data reduction, data presentation, and conclusion drawing/verification. The results of this study found that there is a social construction model in plastic waste management, where from the externalization stage to the objectification stage there is a community empowerment process through the dissemination of ideas and practices for making ecobricks. Meanwhile, from the objectification stage to the internalization stage, there is a regional structuring process which is marked by the establishment of several plastics and eco brick-based parks in the Dusun 15 area of Pematang Johar Village.